Leadership in Global Virtual Teams - Jäppilä, Mikko Matias (My University, 2019)
Due to the development of ICT, the utilization of virtuality has increased rapidly in or-ganizations resulting in using global geographically distributed workforce, operating cross-culturally, operating across different time zones and utilizing only ICT to com-municate. The context of virtuality has changed the context of leadership and the tradi-tional ways of leadership cannot be utilized straight forward. This is why more research on global virtual teams and global virtual team leadership is needed. In addition, the majority of the previous global virtual team research have been conducted by using quantitative research method and in laboratorylike settings with the majority of people from ICT background This thesis analyzes the global virtual teams and global virtual team leadership. The intention of this thesis is to answer what special features global virtual teams have and what is special in global virtual team leadership. The study uses qualitative research method and the empirical part of this thesis was conducted among 5 interviewees who were so called ‘ordinary’ workers from different fields of industry; Human Resources, Marketing, Engineering, Finance and IT. All the interviewees were Finnish and they worked here in Finland by participating in global virtual team projects. This thesis uti-lized abductive approach and semi-structured interview method. The findings of this study are mostly in line with the current global virtual team litera-ture. However, a few notable mentions occur and there are differences, depending on the project and industry, that differ from current academic global virtual team literature. In terms of managerial implications, training and face-to-face meetings are advised in or-der to reduce possible future conflict in global virtual teams. What comes to suggestions for future research, more thorough inspection of specifically focusing in only one of the aspects of virtual leadership is advised.
Keywords: Global Virtual Teams; Virtual Leadership; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business